Perioperative neurocognitive and functional neuroimaging trajectories in older APOE4 carriers compared with non-carriers: secondary analysis of a prospective cohort study. (December 2021) - Browndyke, Jeffrey N.; Wright, Mary C.; Yang, Rosa; Syed, Ayesha; Park, John; Hall, Ashley; Martucci, Katherine; Devinney, Michael J.; Shaw, Leslie; Waligorska, Teresa; Moretti, Eugene W.; Whitson, Heather E.; et al.
Abstract: Background: Cognitive dysfunction after surgery is a major issue in older adults. Here, we determined the effect of APOE4 on perioperative neurocognitive function in older patients. Methods: We enrolled 140 English-speaking patients ≥60 yr old scheduled for noncardiac surgery under general anaesthesia in an observational cohort study, of whom 52 underwent neuroimaging. We measured cognition; Aβ, tau, p-tau levels in CSF; and resting-state intrinsic functional connectivity in six Alzheimer's disease-risk regions before and 6 weeks after surgery. Results: There were no significant APOE4 -related differences in cognition or CSF biomarkers, except APOE4 carriers had lower CSF Aβ levels than non-carriers (preoperative median CSF Aβ [median absolute deviation], APOE4 305 pg ml −1 [65] vs 378 pg ml −1 [38], respectively; P =0.001). Controlling for age, APOE4 carriers had significantly greater preoperative functional connectivity than non-carriers between several brain regions implicated in Alzheimer's disease, including between the left posterior cingulate cortex and left angular gyrus (β [95% confidence interval, CI], 0.218 [0.137–0.230]; P FWE =0.016). APOE4 carriers, but not non-carriers, experienced significant connectivity decreases from before to 6 weeks after surgery between several brain regions including between the left posterior cingulate cortex and left angular gyrus (β [95% CI], –0.196 [–0.256 to –0.136]; P FWE =0.001). Most preoperative and postoperative functional connectivity differences did not change after controlling for preoperative CSF Aβ levels. Conclusions: Postoperative change trajectories for cognition and CSF Aβ, tau or p-tau levels did not differ between community dwelling older APOE4 carriers and non-carriers. APOE4 carriers showed greater preoperative functional connectivity and greater postoperative decreases in functional connectivity in key Alzheimer's disease-risk regions, which occur via Aβ-independent mechanisms.